FLIGHT LEVEL DETERMINATION: CRUISE ALTITUDE ON FUEL CONSUMPTION FOR AIRBUS A320CEO - Audry Farisqi Mosyam; Hafiz Ardian (Pusat Penelitian dan Pengabdian Kepada Masyarakat Politeknik Penerbangan Palembang, 2026)
Fuel efficiency is a critical issue in low-cost carrier operations, particularly on the medium-range Jakarta-Ambon route with high strategic value and load factors. This study evaluates the alignment between flight levels (FL) selected by dispatchers and the optimum FL based on aircraft weight, compares actual fuel consumption with Quick Determination (QDT) simulation results, and analyses how aircraft weight influences fuel efficiency. A descriptive qualitative approach was employed using document analysis, direct observation at the Operation Control Center (OCC), and in-depth interviews with three licensed flight dispatchers. Thirty actual Airbus A320 CEO flight plans for PT. Citilink Indonesia on the Jakarta-Ambon route in November 2024 were analyzed. Results indicate that 76.6% of actual FLs did not match the calculated optimum FL, yielding a fuel penalty of 500-1,558 kg per flight, with an average of approximately 900 kg per deviating flight. Implementing the QDT method enables more precise FL planning based on aircraft weight, contributing to measurable gains in operational fuel efficiency.